Se essa rua fosse minha: ayahuasqueiros e a comunidade Paraíso Tropical Tarumã, Manaus/AM (um estudo das relações de vizinhanças) - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
The basic principle of Sociology asserts that man does not live only the civilizing process shaped him to live within certain patterns of behavior, social structures: streets, neighborhoods, cities, etc., establishing themselves in communities produced livelihoods, built relationships social relations among their neighbors, the social dynamics are nourished by conflict, social coexistence is not always harmonious. On the other hand, sociology does not have a watertight concept of community, common sense infers that being part of a community does not only mean sharing the same neighborhood and geographical location, but the same ideals of solidarity between people who share similar patterns and ideologies, in times of globalization are independent of the geography of the place, just a mobile device, a password and Internet access for a new social relationship to be built. This study involves people, more specifically the Santo Daime ayahuasqueiros and Unity do Vegetal religious groups originating from the Amazon Rainforest in the late 19th and early 20th centuries and their relationships within the place where they live, pray and live on Street Caravele, as well as the Paraíso Tropical Community, an area of disorderly occupations, both established in the Tarumã neighborhood, Manaus/AM, reveals the relations of functional interdependencies through social figurations, based on the theory of Norbert Elias (1897-1990). dances social practices such as solidarity, beneficence or tensions over environmental and religious issues that may interfere with daily life among the subjects of this research. Fixing housing, churches or other social institutions in an area privileged by nature, with natural resources such as streams, environmental reserves, imposes on everyone a leading role in regard to preservation behaviors and attitudes and this is not always synonymous with peace and unity between the neighbors, also deals with stigma, prejudice and intolerance, having as root the (dis) knowledge of modern discourse, perpasses the history and trajectory of the Northeastern Raimundo Irineu Serra and José Gabriel da Costa founders of the ayahuasca religions, in the Amazon during the Cycle of Rubber (1912-1945), brings reflections on the historical clash between science and religion. The research is descriptive, with a qualitative approach, to explore subjective aspects. It contains quantitative aspects by the necessity to quantify the problem and to understand the dimension of this problem, with participant observation both in the rituals of the ayahuasqueiros / hoasqueiros religious groups and in the daily life of the Paraíso Tropical community. Keywords: Ayahuasca, Community, Figurations, Interdependencies, Neighborhood.
Keywords: Ayahuasca; Santo Daime - Amazônia; União do Vegetal - Amazônia; Comunidade - Relações - Amazônia; CIÊNCIAS HUMANAS; Ayahuasca; Comunidade; Figurações; Interdependências; Vizinhanças